Structural basis underlying the synergism of NADase and SLO during group A Streptococcus infection - Wei-Jiun Tsai; Yi-Hsin Lai; Yong-An Shi; Michal Hammel; Anthony P. Duff; Andrew E. Whitten; Karyn L. Wilde; Chun-Ming Wu; Robert Knott; U-Ser Jeng; Chia-Yu Kang; Chih-Yu Hsu; et al. (Communications Biology, 2023)
Structural and mutational analyses reveal interactions between NAD+-glycohydrolase and Streptolysin O critical for Group A Streptococcus virulence, validated in a murine infection model.